PERAN SEKOLAH DALAM SOSIALISASI POLITIK SISWA DI SMA NEGERI 1 PURWODADI - Putri Pratiwi; Yuwanto .; Wiwik W (Journal of Politic and Government Studies, 2015)
AbstractPolitical socialization process is a process to help individual developmentbecome social beings who can adapt well in the society, become good citizens andunderstand their rights and obligations as citizens. School is a venue for theeducational process and part of the political socialization process either directly orindirectly. The overview of process and the result the political socialization inschool, especially in SMA N 1 Purwodadi can be seen from direct politicalsocialization that occurs active learning process in the classroom and indirectpolitical socialization can be seen become a member of an organization in theschool.This research is descriptive quantitative research. The method is surveyresearch method. Survey research method is a research that takes sample fromeone population and using the questionnaire as a primary data collection tool.Based on the results of research on political socialization process inSMAN 1 Purwodadi namely through intrakurukuler activities carried out in theclassroom based civic education curricula related to political issues . In additionthrough intra also performed ekstrakurukuler activities undertaken outside theclassroom such as student council and Scout , with lectures, discussions andsimulations . The material covered is matters related to political issues . Throughboth intra and extra-curricular activities , based on the results of the countingprocess of political socialization in SMAN 1 Purwodadi with an average successrate is as follows : good senagt 37.97 percent , 39.74 percent good , good enough16.00 percent and less either 6.29 percent .In order to create a conducive atmosphere in the government , theadministration and maturation cra understanding of political thinking for theyoung generation is very important . Starting from these objectives in the processof political socialization of the young generation will be more effective if done inschool with a special material that discusses the politics of knowledge containedin the educational curriculum .Keywords : Political socialization, students, SMA N 1 Purwodadi